2004
DOI: 10.1148/radiol.2333031484
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Mammography, Clinical Examination, US, and MR Imaging in Preoperative Assessment of Breast Cancer

Abstract: In nonfatty breasts, US and MR imaging were more sensitive than mammography for invasive cancer, but both MR imaging and US involved risk of overestimation of tumor extent. Combined mammography, clinical examination, and MR imaging were more sensitive than any other individual test or combination of tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
878
9
42

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,288 publications
(970 citation statements)
references
References 61 publications
41
878
9
42
Order By: Relevance
“…Some of these considerations also hold for DCIS. Moreover, variable sensitivity of MRI for the detection of pure DCIS has been observed in other studies [10,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Some of these considerations also hold for DCIS. Moreover, variable sensitivity of MRI for the detection of pure DCIS has been observed in other studies [10,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 69%
“…Conventional imaging by mammography and ultrasonography fails to accurately assess tumor extent in approximately one-third of patients eligible for BCT [7]. Several studies reported a higher sensitivity of contrastenhanced magnetic resonance imaging (CE MRI) to detect invasive breast cancer and to visualize disease extent compared to the standard workup using conventional imaging [8][9][10][11]. These observations have led to changes in the surgical management of patients [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…MRI of the breast has obtained a prominent role in clinical practice because of its high sensitivity for detecting invasive breast tumors (1)(2)(3). However, the specificity of DCE MRI of the breast, is substantially lower.…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 99%
“…However, the specificity of DCE MRI of the breast, is substantially lower. It was shown to reach approximately 70% (1)(2)(3). Many different strategies have been proposed to increase the specificity such as calculating pharmacokinetic contrast parameters (4), T2*-weighted perfusion imaging (5) and MR spectroscopy (5).…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 99%
“…In addition, these improvements have allowed expansion of the indications for use of breast ultrasound (US), including tumor differentiation, preoperative staging, follow-up after cancer treatment, and interventional diagnosis [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%